THE NUMBER OF ZERO SOLUTIONS FOR COMPLEX CANONICAL DIFFERENTIAL EQUATION OF SECOND ORDER WITH CONSTANT COEFFICIENTS IN THE FIRST QUADRANT - Vujakovic, Jelena; Rajović, Miloje (Bulletin of Natural Sciences Research, 2016)
The study of complex differential equations in recent years has opened up some of questions concerning the determination of the frequency of zero solutions, the distribution of zero, oscillation of the solution, asymptotic behavior, rank growth and so on. Besides, this is solved by only some classes of differential equations. In this paper, our aim was to determine the number of zeros and their arrangement in the first quadrant, for the complex canonical differential equation of the second order. The accuracy of our results, we illustrate with two examples.
Keywords: differential equations; function of frequency; sine solution; cosine solution; zero solutions